Students Perception of the English Intensive Program in Improving Non-English Majored Students Speaking Performance - Ubaedillah Ubaedillah; Budi Adjar Pranoto; Yuniar Fatmasari (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
This study aims to determine students' perception of the English Intensive Program (EIP) in improving students' speaking performance. The Cross-sectional survey design was designed to analyze a detailed and in-depth analysis using google forms to distribute the research questionnaires. The researcher used two instruments to find the required data and determine students' perception of EIP, namely questionnaires and speaking performance test reports. The researcher combined the two instruments to support the research data. Researchers recruited 40 students as samples from non- English departments. The findings show that after implementing the EIP, the students' speaking performance experienced a significant increase of 74.12, which means EIP positively impacts improving students' speaking performance. In addition, the student's perception of EIP was 88.2% strongly agree and agree, which means the implementation of EIP in improving students' speaking performance is EIP functions effectively.